2010
DOI: 10.1007/s10021-010-9380-z
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Redfield Ratio and a Family of Nutrient Limitation Indicators as Thresholds for Phytoplankton N vs. P Limitation

Abstract: We aim to define the best nutrient limitation indicator predicting phytoplankton biomass increase as a result of nutrient enrichment (N, P, or both). We compare the abilities of different indicators, based on chemical measurements of nitrogen (N) and phosphorus (P) fractions in the initial plankton community, to predict the limiting factor for phytoplankton growth as inferred independently from short-term laboratory experiments on the same natural communities in a data set from NE Baltic Sea (Tamminen and And… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
109
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(118 citation statements)
references
References 27 publications
6
109
0
3
Order By: Relevance
“…Then, models for quantitative relationships between loads and these parameters are needed to estimate the maximum acceptable loads required to reach these target values. Recent research has demonstrated that dual-nutrient (N, P) reduction strategies are needed to alleviate eutrophication in estuaries and other coastal waters in the land-sea continuum (Boynton and Kemp, 2008;Conley et al, 2009;Paerl, 2009), and that the Redfield ratio for N and P in marine waters (16 : 1, molar) cannot be considered a universally optimal ratio between N and P, but rather an average of species-specific N : P ratios (Klausmeier et al, 2004;Ptacnik et al, 2010).…”
Section: Estimate Of Maximum Acceptable Loadsmentioning
confidence: 99%
“…Then, models for quantitative relationships between loads and these parameters are needed to estimate the maximum acceptable loads required to reach these target values. Recent research has demonstrated that dual-nutrient (N, P) reduction strategies are needed to alleviate eutrophication in estuaries and other coastal waters in the land-sea continuum (Boynton and Kemp, 2008;Conley et al, 2009;Paerl, 2009), and that the Redfield ratio for N and P in marine waters (16 : 1, molar) cannot be considered a universally optimal ratio between N and P, but rather an average of species-specific N : P ratios (Klausmeier et al, 2004;Ptacnik et al, 2010).…”
Section: Estimate Of Maximum Acceptable Loadsmentioning
confidence: 99%
“…2). On the contrary, Ptacnik et al (2010) found seston N:P to be the poorest, among a suite of indicators, to predict nutrient limitation, which at least in part is explained by the mixed nature of seston composition. Phytoplankton does not obey homeostatic rules in their elemental household, but rather show, at least in cultures, strong variability in their C:P and N:P (less for C:N) ratios depending on growth conditions (cf.…”
Section: Seasonal Variation In Seston Concentrations and Ratiosmentioning
confidence: 99%
“…Our data is in support of Marañón (2005), who based on studies of phytoplankton growth rates in the subtropical areas of the north Atlantic, concluded that the frequent observation of seston C:N-ratios close to Redfield even in situations with slow growing, nutrient limited phytoplankton could be accredited bacterial and detrital contributions to seston. One should therefore be careful in interpreting sestonic C:N-ratios as indicators of nutritional status of phytoplankton, as also emphasized by Ptacnik et al (2010).…”
Section: Variable Sestonic Composition May Stabilize Elemental Ratiosmentioning
confidence: 99%
“…In contrast, 70% of DSi/DIP atomic ratios were higher than the Si/P ratio of freshwater diatoms. However, Ptacnik et al (2010) concluded the ratio of DIN to TP as the best performing indicator for phytoplankton N versus P limitation considering the availability, suggesting that the DSi/DIN ratio is the adequate indicator for inferring nutrient limitations, but not the DSi/DIP ratio. These findings suggest that DSi might be one of the main factors limiting the growth of diatoms in the lake during a bloom season.…”
Section: Discussion Nutrient Limitation For Diatomsmentioning
confidence: 97%